The Phonetic Challenges of English for Javanese Speakers - Ayuna Junaida, Alfian (Maliki Interdisciplinary Journal, 2025)
This article discusses the phonetic challenges experienced by Javanese learners of English as a foreign language. The research identifies various types of phonological interference, including issues with consonant pronunciation and the use of diphthongs and monophthongs, as well as segmental and suprasegmental aspects such as intonation and stress. These errors primarily stem due to the differences between the phonological systems of Javanese as a first language (L1) and English as a foreign language (L2), resulting in phonological transfer. Other factors besides pronunciation include a lack of confidence due to the ’medhok’ stereotype regarding Javanese speakers. Furthermore, factors that hinder learning include non-linguistic elements such as age and the learning environment. The article concludes that improving pronunciation requires a combination of phonetic instruction, consistent practice and a supportive learning environment.